Development of Interactive Media Articulate Storyline 3 on Earth Structure Material to Improve Elementary School Students' Science Learning Outcomes - Syo’immatun Nisa’; Sigit Yulianto (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop, test the feasibility and effectiveness of interactive learning media Articulate Storyline 3 to improve learning outcomes in grade V students at SDN Sembaturagung 02 Pati Regency. This type of research is development research (R&D) using the Borg and Gall model. The subjects of this study were grade V students of SDN Sembaturagung 02 totaling 29 students in the 2024/2025 academic year. Data collection techniques used test techniques (pretest-posttest) and non-tests in the form of observation, interviews, questionnaires, and documentation. The results of this study indicate that the development of interactive media Articulate Storyline 3 is effective in improving the science learning outcomes of grade V students of SDN Sembaturagung 02 Pati Regency. This is evident from the results of the feasibility test obtained by the percentage of assessment by material experts, namely 90.20% and media experts 92.50% with the criteria "very feasible". The effectiveness of the Articulate Storyline 3 media is proven by the average increase in posttest results with the results of the N-gain test of 0.50 which is in the moderate category. Teachers and students gave very positive responses to the distributed questionnaire. Based on these results, it shows that the interactive media Articulate Storyline 3 is effective in improving student learning outcomes and is feasible and useful for use in science learning on the material of the structure of the earth's layers in class V SDN Sembaturagung 02.